Evaluación de diferentes fuentes de fibra en el depósito de grasa en pollos de carne, bajo sistemas de producción en altura - Herrera Pardo, Bryan Patricio (2024)
The inclusion of dietary fiber is considered essential due to its key role in promoting digestive health, boosting the immune response, alleviating metabolic disorders, and facilitating nutrient absorption. This study is designed to determine the effect of different dietary fiber sources on fat accumulation in broilers raised at altitude. Four hundred 45-day-old broilers of the Cobb 500 line, with an average weight of 1127.64 grams, are randomly allocated into four treatments: T1 (control), T2 (wheat bran), T3 (rice hulls), and T4 (palm kernels). A fully randomized design is employed, with diets formulated strictly to the established nutritional requisites for the Cobb 500 line throughout every production stage. The evaluation of abdominal fat and liver fat is performed. Statistical analysis is conducted using the SAS 2016 software, with means compared using the Tukey test. The results indicate that there is no significant difference (p=0.171) in abdominal fat among treatments utilizing different fiber sources, with an average value of 0.66%. However, a statistically significant difference (p=<0.001) is observed in liver fat content. Specifically, the inclusion of 18% wheat bran resulted in a lower fat content of 7.45%, whereas the highest fat content is recorded with the inclusion of rice hulls, reaching values of 14.3%. It is concluded that the inclusion of fiber sources did not have a significant effect on the deposition of abdominal fat; however, a negative effect on liver fat deposition is observed with the inclusion of rice hulls.